2020
DOI: 10.1038/s41385-020-0277-7
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in the glycosyltransferase Gcnt1 increases susceptibility to tuberculosis through a mechanism involving neutrophils

Abstract: Modulation of immunity and disease by glycans is increasingly recognized. However, how host glycosylation shapes and is shaped by tuberculosis remains poorly understood. We show that deficiency in the glucosaminyl (N-acetyl) transferase 1 (Gcnt1), a key enzyme for core-2 O-glycans biosynthesis, drives susceptibility to Mycobacterium tuberculosis infection. The increased susceptibility of Gcnt1 deficient mice was characterized by extensive lung immune pathology, mechanistically related to neutrophils. Uninfecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 58 publications
2
28
0
Order By: Relevance
“…Interestingly, a recent knockout study found that GCNT1 deficient mice have neutrophilia and increased susceptibility to tuberculosis infection. The increased susceptibility of GCNT1 deficient mice to infection was largely driven by exacerbated neutrophil counts, which led to lung lesions, inflammation, and other pathologic features in the lungs of affected mice 31 . This link between GCNT1 and neutrophilia is relevant to studying the regulation of IgE as other studies have shown elevated serum IgE levels to be associated with neutrophilic asthma 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent knockout study found that GCNT1 deficient mice have neutrophilia and increased susceptibility to tuberculosis infection. The increased susceptibility of GCNT1 deficient mice to infection was largely driven by exacerbated neutrophil counts, which led to lung lesions, inflammation, and other pathologic features in the lungs of affected mice 31 . This link between GCNT1 and neutrophilia is relevant to studying the regulation of IgE as other studies have shown elevated serum IgE levels to be associated with neutrophilic asthma 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Mice were infected with M. tuberculosis H37Rv or HN878 strains via aerosol route using an inhalation exposure system (Glas-Col), following previously published protocols [ 15 ]. A murine model of active TB mimicking human TB was used, as described in Kroesen et al [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…infection (4 × 10 4 –2 × 10 5 CFU/mL per mouse) with M. tuberculosis H37Rv Pasteur strain. At the experimental time points (15, 30, 60 and 90 days post-infection), the lungs of infected animals were harvested and the bacterial load determined by CFU enumeration, as previously described [ 15 , 25 , 26 ]. The data is presented in Supplementary Figure S1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations